Pemodelan Daerah Genangan Banjir Ekstrem Bendung Sungai Piam Kabupaten Langkat Provinsi Sumatera Utara - Zevri, Asril (JURNAL SUMBER DAYA AIR, 2025)
The construction of the Piam River weir is one of the efforts to support food security for the community, especially in Langkat Regency. Increased water levels in the rainy season with high intensity and long duration can cause rapid changes in the return flow with large volumes in the upper reaches of the river. Changes in the return flow can cause flooding in the river plain, resulting in a risk of loss to the community. One of the initial nonstructural efforts in flood mitigation is to delineate flood inundation areas through hydraulic simulation modelling based on the 100-year return period maximum flood discharge, longitudinal and transverse river profiles, and weir profiles. Modelling simulations were carried out using HEC RAS Software in a 2-dimensional manner based on 100-year return period flood discharge data as boundary conditions upstream, DEMNAS as a base map of the river geometry profile, and weir dimensions as boundary conditions downstream. The results of modeling the flood inundation area with a 100-year return period flood discharge of 239.66 m3/det show that the maximum potential flood water level reaches 3 m inundating the plain area up to 500 m from the river bank. The flood inundation area that occurs reaches 390.21 ha so that flood control efforts are needed by building embankments and normalizing the river upstream of the weir.